SARS-CoV-2 and chronic myeloid leukemia: a systematic review - Ali, Elrazi A.; Al-Sadi, Anas; Al-maharmeh, Qusai; Subahi, Eihab A.; Bellamkonda, Amulya; Kalavar, Madhumati; Panigrahi, Kalpana; Alshurafa, Awni; Yassin, Mohamed A. (Frontiers in Medicine, 2024)
The major limitation of this review is the lack of details about the use or hold of TKIs during SARS-CoV-2 infection. Additionally, after the appearance of the different variants of the SARS-CoV-2 virus, few studies mentioned the variant of the virus, which makes it difficult to compare the outcome of the other variants of the SARS-CoV-2 virus in patients with CML. Despite the limitations of the study, CML patients with COVID-19 haves no significant increase in mortality compared to other hematological malignancy. Hematological cancers are associated with an increased risk of thrombosis, which is expected to increase in patients with COVID-19. However, patient with CML has not been reported to have a significant increase in thrombosis risk. The available data indicates that COVID-19's effect on patients with chronic myeloid leukemia (CML) still needs to be better understood due to the limited data.